Diacylglycerol kinase as a possible therapeutic target for neuronal diseases - Shirai, Yasuhito (BioMed Central, 2014)
Diacylglycerol kinase (DGK) is a lipid kinase converting diacylglycerol to phosphatidic acid, and regulates many enzymes including protein kinase C, phosphatidylinositol 4-phosphate 5-kinase, and mTOR. To date, ten mammalian DGK subtypes have been cloned and divided into five groups, and they show subtype-specific tissue distribution. Therefore, each DGK subtype is thought to be involved in respective cellular responses by regulating balance of the two lipid messengers, diacylglycerol and phosphatidic acid. Indeed, the recent researches using DGK knockout mice have clearly demonstrated the importance of DGK in the immune system and its pathophysiological roles in heart and insulin resistance in diabetes. Especially, most subtypes show high expression in brain with subtype specific regional distribution, suggesting that each subtype has important and unique functions in brain. Recently, neuronal functions of some DGK subtypes have accumulated. Here, we introduce DGKs with their structural motifs, summarize the enzymatic properties and neuronal functions, and discuss the possibility of DGKs as a therapeutic target of the neuronal diseases.